Defining patient communication needs during hospitalization to improve patient experience and health literacy - Guillem Marca-Frances; Joan Frigola-Reig; Jesica A. Menéndez-Signorini; Marc Compte-Pujol; Eulàlia Massana-Morera (BMC, 2020)
Abstract Background In order to play an active role in their health care, patients need information and motivation. Current delivery systems limit patients' involvement because they do not routinely provide them with enough details of their own clinical results, conditions and other important clinical data. The purpose of this study was to identify, from the perspective of patients, which topics matter the most, who should be communicating them, and when and how should they be provided. Methods We conducted a qualitative, phenomenological study analysing the content of subjective experiences, feelings and behaviours. We organized two focus groups with 13 participants and 15 in-depth interviews. Transcripts of the focus groups and interviews were checked for accuracy and then entered into Atlas ti™ v7.5.13 qualitative software. Two independent researchers performed a qualitative inductive content analysis to classify the data in two levels: themes and categories. Results The qualitative analysis provided 377 units of meaning synthesized into 22 categories and six themes: hospitalization procedure, Health Literacy relating to the patient's condition, information content, satisfaction, professional-patient relationship, and patient proactivity. Patients described which information they wished for, when they needed it, and who would provide it, usually related to actions such as admission, discharge or diagnostic tests. Oral information was more difficult to comprehend than the written kind, as patients can check written information several times if needed. Nurses were the most available professionals, and patients found easier to relate to them and ask them questions. Moreover, patients identified physicians as those professionals responsible for providing clinical information. Conclusions Our results showed that patients suffered from poor Health Literacy regarding their personal condition, as they were unable to describe the symptoms, the type of tests being performed or their results, and some of them also had difficulties in naming the specific disease or comorbidities they had. During the hospitalization process, patients were in good shape to come with doubts and actively asked for more information. Healthcare organizations and professionals were offered the chance to ensure the correct communication and comprehension to their patients.